A new method for calculating fuel consumption and displacement of a ship in maritime transport. Issue 1 (1st January 2017) - Mersin, Kadir; Alkan, Güler; Mısırlıoğlu, Tunç
Abstract: Fuel consumption is the most important parameter which is effected by the petrol prices. Optimization of the sailing speed decreases the fuel cost because it is proportional to the sailing speed. In this study, the present fuel consumption formula has been improved by finding a formula that shows the change of the displacement of the ship according to the time.